Receptor for hyaluronic acid- mediated motility (RHAMM) regulates HT1080 fibrosarcoma cell proliferation via a β-catenin/c-myc signaling axis - Kouvidi, Katerina; Berdiaki, Aikaterini; Tzardi, Maria; Karousou, Evgenia; Passi, Alberto; Nikitovic, Dragana; Tzanakakis, George N. (Biochimica et biophysica acta, 2016)
High levels of hyaluronan (HA) synthesis in various cancer tissues, including sarcomas, are correlated with tumorigenesis and malignant transformation. RHAMM (receptor for hyaluronic acid-mediated motility) is overexpressed during tumor development in different malignancies. β-Catenin is a crucial downstream mediator of the Wnt signaling cascade which facilitates carcinogenic events characterized by deregulated cell proliferation. Real-time PCR, in vitro cell proliferation assay, siRNA transfection, flow cytometry, immunoprecipitation, western blotting and immunofluorescence were utilized. The reduction of RHAMM expression was strongly correlated with an inhibition of HT1080 fibrosarcoma cell growth (p≤0.01). LMWHA, in a RHAMM-dependent manner increases cell growth of HT1080 cells ((p≤0.01). Both basal and LMWHA dependent growth of HT1080 cells was attenuated by β-catenin deficiency (p≤0.01). β-Catenin cytoplasmatic deposition is positively regulated by RHAMM (p≤0.01). Immunoflourescence and immunoprecipitation suggest that RHAMM/β-catenin form an intracellular complex. Transfection experiments identified c-myc as candidate downstream mediator of RHAMM/β-catenin effects on HT1080 fibrosarcoma cell proliferation. LMWHA/RHAMM downstream signaling regulates fibrosarcoma cell growth in a β-catenin/c-myc dependent manner. The present study suggests that RHAMM is a novel β-catenin intracellular binding partner, protecting β-catenin from degradation and supporting the nuclear translocation of this key cellular mediator, which results in c-myc activation and enhanced fibrosarcoma cell growth. •Hyaluronan (HA) regulates crucial cancer cell functions through interactions with its RHAMM and CD44 receptors.•Low molecular weight HA (LMWHA) enhances RHAMM expression to increase (p≤0.01) HT1080 cells' growth.•RHAMM/β-catenin complex formation increases β-catenin intracellular pool.•LMWHA/RHAMM actions regulate fibrosarcoma cell proliferation via a β-catenin/c-myc signaling pathway.